Prognostic benefit from an early invasive strategy in patients with non ST elevation acute coronary syndrome (NSTEACS): evaluation of the new risk stratification in the NSTEACS European guidelines. (14th October 2021) - Martinon-Martinez, J; Alvarez Alvarez, B; Gonzalez Ferrero, T; Garcia-Rodeja Arias, F; Otero Garcia, O; Cacho Antonio, C; Abou Jokh Casas, C; Cordero, A; Cid Alvarez, B; Iglesias Alvarez, D; Agra Bermejo, R; Rigueiro Veloso, P; et al.
Abstract: Objectives: The objective of our work is to evaluate the prognostic benefit of an early invasive strategy in patients with high-risk NSTACS according to the recommendations of the 2020 clinical practice guidelines during long-term follow-up. Methods: This retrospective observational study included 6454 consecutive NSTEACS patients. We analyze the effects of early coronary angiography (<24 h) in patients with: (a) GRACE risk score >140 and (b) patients with "established NSTEMI" (non ST-segment elevation myocardial infarction defined by an increase in troponins) or dynamic ST-T-segment changes with a GRACE risk score <140. Results: From 2003 to 2017, 6454 patients with "new high-risk NSTEACS" were admitted, and 6031 (93.45%) of these underwent coronary angiography. After inverse probability of treatment weighting, the long-term cumulative probability of being free of all-cause mortality, cardiovascular mortality and MACE differed significantly due to an early coronary interven- tion in patients with NSTEACS and GRACE >140 [HR 0.62 (IC 95% 0.57–0.67), HR 0.62 (IC 95% 0.56–0.68), HR 0.57 (IC 95% 0.53–0.61), respectively]. In patients with NSTEACS and GRACE <140 with established NSTEMI or ST/T-segment changes, the benefit of the early invasive strategy is only observed in the reduction of MACE [HR 0.62 (IC 95% 0.56–0.68)], but not for total mortality [HR 0.96 (IC 95% 0.78–1.2)] and cardiovascular mortality [HR 0.96 (IC 95% 0.75–1.24)]. Conclusions: An early invasive management is associated with reduced all-cause mortality, cardiovascular mortality and MACE in NSTEACS with high GRACE risk score. However, this benefit is less evident in the subgroup of patients with a GRACE score <140 with established NSTEMI or ST/T-segment changes. Funding Acknowledgement: Type of funding sources: None.